Valence hole subbands and optical gain spectra of GaN/Ga1-xAlxN strained quantum wells - Li, M. F. (2013)
The valence hole subbands, TE and TM mode optical gains, transparency carrier density, and radiative current density of the zinc‐blende GaN/Ga0.85Al0.15N strained quantum well (100 Å well width) have been investigated using a 6×6 Hamiltonian model including the heavy hole, light hole, and spin‐orbit split‐off bands. At the k=0 point, it is found that the light hole strongly couples with the spin‐orbit split‐off hole, resulting in the so+lh hybrid states. The heavy hole does not couple with the light hole and the spin‐orbit split‐off hole. Optical transitions between the valence subbands and the conduction subbands obey the Δn=0 selection rule. At the k≠0 points, there is strong band mixing among the heavy hole, light hole, and spin‐orbit split‐off hole. The optical transitions do not obey the Δn=0 selection rule. The compressive strain in the GaN well region increases the energy separation between the so1+lh1 energy level and the hh1 energy level. Consequently, the compressive strain enhances the TE mode optical gain, and strongly depresses the TM mode optical gain. Even when the carrier density is as large as 1019 cm−3, there is no positive TM mode optical gain. The TE mode optical gain spectrum has a peak at around 3.26 eV. The transparency carrier density is 6.5×1018 cm−3, which is larger than that of GaAs quantum well. The compressive strain overall reduces the transparency carrier density. The J rad is 0.53 kA/cm2 for the zero optical gain. The results obtained in this work will be useful in designing quantum well GaN laser diodes and detectors.